Una vita come campo trascendentale impersonale. La ricezione deleuziana di Ruyer - Tosel, Natascia (Philosophy Kitchen - Rivista di filosofia contemporanea, 2016)
This article stages an encounter between Gilles Deleuze and Raymond Ruyer on the question of the subject. Most of the article is spent developing Ruyer’s concept of subjectivité sans sujet, which characterizes the consciousness, in order to show how this notion has influenced Deleuze and his idea of an impersonal and pre-individual transcendental field.